Relationship between physical activity and nutritional status of pre-school children - Yusof, Nurul Ashikien Md (Universiti Sains Malaysia, 2016)
Limited research has been conducted to determine the level of physical activity and nutrition levels of pre-school children. However, this study is the first to be carried out in order to determine the level of physical activity and nutrition levels among Malaysian pre-school children between the age of 4 to 6 years old. It is important to determine the factors which can determine the health status and the obesity rale among children in future and also make sure the next generation to be more productive in our country Malaysia. The aim of this study was to investigate the relationship between levels of physical activity and nutrition status among pre-school children from aged between 4 to 6 years old in Malaysia. The subjects recruited were 33 children from age 4 to 6 years, including boys and girls in the National Child Development Research Center (NCDRC), Universiti Pendidikan Sultan Idris (UPSI) in Perak, Anthropometric of height and measurements weight, measurement of physical activity level by Accelerometer, 24-hours recall and food records was obtained during the visit . Their subjects BM1 were then calculated from their height and weight. Results indicated that the level of physical activity involved most was of sedentary activity and very vigorous activity was the least. It was also show that was differences between the boys and girls, the boys were more active than the girls. In addition, the results also showed that children at age 4 years old were more than children active between 5 to 6 years old. Results showed that the total steps of children have no correlation with total Calories intake (r = 0.19, p = 0.29). From the result obtained, it can be concluded that deceased levels of physical activity lead to excess weight and if it sustained can lead to be obesity among pre-school children. It could also affect negatively health among pre-school children, especially those in aged between 4 to 6 years old.